SISTEM PEMBERITAHUAN SURAT OTOMATIS MELALUI SMS - , ADHITYA HERMAN P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Letter notification system via sms based Arduino Uno R3 have been made to facilitate the monitoring mailbox. This system consists of a Photodiode, Arduino and GSM sim900shield. Incoming mail and legible letters on the sensor will be displayed via Mobile phone and LCD. The results of this study is an automatic notification via SMS inbox that implemented using the Arduino Uno R3 and GSM sim900shield.photodiode sensor placed in the mailbox to find a letter inside. The system will work according to its function if more than one photodiode sensor is blocked by obstacles. This tool was created to facilitate monitoring mailbox because Someone who will monitoring that should be in front of the equipment, so the persononly can monitoring at the time and near the equipment. This causes the monitoring process to be inefficient and ineffective.